The generation of transmedia content from the analysis of the image in tourism, an approach to the publication in social networks (2022)
The aim of this article is to make the different components of the tourism product visible through a promotional strategy that reflects the different factors of the image and brings a possible consumer closer to a first impression of the destination. Therefore, by using the social network Instagram and generating transmedia content, the aim is not only to promote tourism but also to address elements that arise from tourism research, using social networks as a socializing mechanism for the activity. The publications and structural elements that are considered when making a specific tourist destination visible are presented. This article is the result of joint work between the Tourism Experiences Classroom and the TourismMente Seedbed.